Multifunction Green Open Space for Environmental Education - Ika Dewi, Riyawati; Sya, Ahman; Vivanti, Diana (KnE Social Sciences, 2020)
With huge pressures from a rapidly growing population, Jakarta suffers from an increasingly low Environmental Quality Index (IKLH). In 2016 and 2017 it was the only province in Indonesia with the IKLH index “alert” according to the Ministry of Environmental and Forestry. Improving the quantity and quality of Green Open Space (GOS) is one way to counter this issue, and this initiative is undertaken by the DKI Jakarta Government to improve the quality of its environment. However, land limitations remain a challenge. The solution of the DKI Jakarta Government is to create multifunction GOS that combine various interests and facilities. The purpose of this study is to identify potential educational benefits from multifunction GOS, using qualitative analysis via literature study. The results suggest that the GOS provide economic, social and educational improvements. Most of the articles said that education through GOS is the second benefit that people can get. This study concludes that GOS can serve to improve environmental awareness in visitors, via indirect educational methods. Keywords: Green Open Space, Multifunction Green Open Space, Environmental Education